On T cell development, T cell signals, T cell specificity and sensitivity, and the autoimmunity facilitated by lymphopenia. (7th May 2020) - Bretscher, Peter A.; Al‐Yassin, Ghassan; Anderson, Colin C.
Abstract: We propose a framework to explain how T cells achieve specificity and sensitivity, how the affinity of the TcR peptide/MHC interaction controls positive and negative thymic selection and mature T cell survival, and whether antigen‐dependent activation and inactivation takes place. Two distinct types of signalling can lead to mature T cell multiplication. One requires the TcR to recognize with a certain affinity an antigen‐derived peptide, an agonist peptide, bound to an MHC molecule. The other, the tonic signal, leads to naïve T cell survival and modest proliferation if the T cell successfully competes for endogenous, self‐peptide/MHC ligands, involving lower affinity TCR/ligand interactions. Many suggest lymphopenia contributes to autoimmunity by increasing the strength of TcR‐tonic signalling, and so activation of anti‐self T cells. We suggest T cell activation requires antigen‐mediated cooperation between T cells. Increased tonic signalling under lymphopenic conditions facilitates T cell proliferation and so antigen‐dependent cooperation and activation of anti‐self T cells.